CAF-like state in primary skin fibroblasts with constitutional BRCA1 epimutation sheds new light on tumor suppressor deficiency-related changes in healthy tissue. Issue 2 (1st February 2016) - Etzold, Anna; Galetzka, Danuta; Weis, Eva; Bartsch, Oliver; Haaf, Thomas; Spix, Claudia; Itzel, Timo; Schweiger, Susann; Strand, Dennis; Strand, Susanne; Zechner, Ulrich
ABSTRACT: Constitutive epimutations of tumor suppressor genes are increasingly considered as cancer predisposing factors equally to sequence mutations. In light of the emerging role of the microenvironment for cancer predisposition, initiation, and progression, we aimed to characterize the consequences of a BRCA1 epimutation in cells of mesenchymal origin. We performed a comprehensive molecular and cellular comparison of primary dermal fibroblasts taken from a monozygous twin pair discordant for recurrent cancers and BRCA1 epimutation, whose exceptional clinical case we previously reported in this journal. Comparative transcriptome analysis identified differential expression of extracellular matrix-related genes and pro-tumorigenic growth factors, such as collagens and CXC chemokines. Moreover, genes known to be key markers of so called cancer-associated fibroblasts (CAFs), such as ACTA2, FAP, PDPN, and TNC, were upregulated in fibroblasts of the affected twin ( BRCA1 mosMe ) in comparison to those of the healthy twin ( BRCA1 wt ). Further analyses detected CAF-typical cellular features, including an elevated growth rate, enhanced migration, altered actin architecture and increased production of ketone bodies in BRCA1 mosMe fibroblasts compared to BRCA1 wt fibroblasts. In addition, conditioned medium of BRCA1 mosMe fibroblasts was more potent than conditioned medium of BRCA1 wt fibroblasts to promote cell proliferation in an epithelial and a cancer cell line. Our data demonstrate, that a CAF-like state is not an exclusive feature of tumor-associated tissue but also exists in healthy tissue with tumor suppressor deficiency. The naturally occurring phenomenon of twin fibroblasts differing in their BRCA1 methylation status revealed to be a unique powerful tool for exploring tumor suppressor deficiency-related changes in healthy tissue, reinforcing their significance for cancer predisposition.